Protesting Human Life Amendment; Supporting Women's Right to Choice by State Building on Mariposa Mall - Watkins, Howard::::::::: (1981)
Protesters walking in large circle holding signs: "No HLA in California or the USA: "Keep Abortion Legal" "A Child's Right To Be Wanted;;A Woman's Right To Choose"